Clinical, Magnetic Resonance Imaging, and Histopathologic Findings in 6 Dogs with Surgically resected Extraparenchymal Spinal Cord Hematomas. (January 2015) - Hague, D.W.; Joslyn, S.; Bush, W.W.; Glass, E.N.; Durham, A.C.
<x xml:space="preserve">Abstract</x> Background Extraparenchymal spinal cord hematoma has been described in veterinary medicine in association with neoplasia, intervertebral disk disease, and snake envenomation. There are rare reports of spontaneous extraparenchymal spinal cord hematoma formation with no known cause in human medicine. Multiple cases of spontaneous extraparenchymal spinal cord hematoma have not been described previously in veterinary medicine. Objectives To describe the signalment, clinical findings, magnetic resonance imaging (MRI) features, and surgical outcomes in histopathologically confirmed extraparenchymal spinal cord hematomas in dogs with no identified underlying etiology. Animals Six dogs had MRI of the spinal cord, decompressive spinal surgery, and histopathologic confirmation of extraparenchymal spinal cord hematoma not associated with an underlying cause. Methods Multi‐institutional retrospective study. Results Six patients had spontaneous extraparenchymal spinal cord hematoma formation. MRI showed normal signal within the spinal cord parenchyma in all patients. All hematomas had T2‐weighted hyperintensity and the majority (5/6) had no contrast enhancement. All dogs underwent surgical decompression and most patients (5/6) returned to normal or near normal neurologic function postoperatively. Follow‐up of the patients (ranging between 921 and 1, 446 days) showed no progression of neurologic clinical signs or any conditions associated with increased bleeding tendency. Conclusions and Clinical Importance Before surgery and histopathology confirming extraparenchymal hematoma, the primary differential in most cases was neoplasia, based on the MRI findings. This retrospective study reminds clinicians of the importance of the combination of advanced imaging combined with histopathologic diagnosis. The prognosis for spontaneous spinal cord extraparenchymal hematoma with surgical decompression appears to be favorable in most cases.